Assessing Responsibility for Program Output: We lack an easy way to indicate that algorithms do not make decisions and are not biased; programmers do, and are. - Hill, Robin K. (Communications of the ACM, 2018)
The article discusses the decision making capacity of algorithms, computer programs and computer programmers, contending that algorithms are not involved in decision making. An overview of the responsibility of computer-related problems, including responsibility attributed to programmers and computer programs, is provided.